The Ashtanga Yoga Paradigm: Frameworks for Holistic Health and Well-Being - Singh, Priti; Jain, Rahul; Kulkarni, Medha (International Research Journal of Ayurveda & Yoga, 2026)
Health encompasses multiple dimensions, including physical, mental, social, spiritual, and emotional aspects, extending beyond the mere absence of disease. The term “Yoga” originates from the concept of union, connection, or completeness. It serves as a pathway to reconnect with our inner selves, particularly when our lives are consumed by external demands. Yoga facilitates the alignment of our body, mind, and soul, offering control over the Chitta Vrittis, the waves of thoughts that the mind craves. It fosters stability within our physical and mental being, bringing harmony to our thoughts. Yogic practices address the holistic well-being of the mind, body, and soul. Yoga should not be reduced to a set of postures used solely for weight loss; postures, or asanas, are just one component. The Ashtanga Yoga system outlined in texts comprises eight limbs: Yama (social discipline) and Niyama (individual discipline) dictate the principles governing one’s life and influence social well-being. Asana and Pranayama have direct impacts on physical and mental health, regulating and revitalizing the body. Pratyahara (withdrawal from senses) maintains control over the body and mind, preventing the senses from indulging in harmful desires that can lead to physical disorders. Dharana (concentration) enhances the balance between the mind and body, while Dhyana (meditation) reinforces our ability to cope with stress, safeguarding both mental and physical health. Collectively, Dharana, Dhyana, and Samadhi contribute positively to one’s spiritual and emotional health. It’s essential to practice all eight components of Yoga, not just the physical postures. In today’s world, where stress is prevalent, dietary habits are often flawed, and environmental pollution abounds, these factors collectively impact all facets of health. Yoga serves as a comprehensive approach to enhance and maintain overall well-being, offering strength to the body and joy to the senses. This paper will delve into these aspects in greater detail.